COVID-19 eviction moratoriums and eviction filings: evidence from New Orleans. Issue 1 (2nd January 2022) - Callison, Kevin; Finger, Davida; Smith, Isabella M.
ABSTRACT: Securing stable housing to prevent the spread of infection during the COVID-19 pandemic remains a concern among policymakers in the US. In this article, we provide a descriptive analysis of the association between COVID-19-related eviction moratoriums and eviction filings in New Orleans, Louisiana. Beginning in March 2020, four separate moratoriums were implemented at the local, state, and federal levels that sought to restrict eviction filings in New Orleans. We collected data on evictions filed from January 2017 through November 2020 in the First City Court of Orleans Parish, the entity responsible for adjudicating the majority of eviction filings in New Orleans. We then examined the association between the various eviction moratoriums, the number of evictions filed, the estimated number of evictions temporarily averted, and the average suit dollar amount for filed evictions. Our results indicate that local and state moratoriums were effective at temporarily halting eviction filings. Federal moratoriums offering fewer protections reduced eviction filings by approximately 50%. We estimate that COVID-19-related eviction moratoriums temporarily averted 2, 492 eviction filings in New Orleans between March and November 2020. The average suit amount for eviction filings that resumed following the expiration of local and state moratoriums doubled from pre-COVID-19 filing amounts.